2015
DOI: 10.1542/peds.2015-1677
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disordered Breathing and Academic Performance: A Meta-analysis

Abstract: Variable definitions of both academic performance and SDB likely contributed to the heterogeneity among published investigations. Clear links between SDB and poorer academic performance in school-age children are demonstrated. ES statistics were in the small to medium range, but nevertheless the findings serve to highlight to parents, teachers, and clinicians that SDB in children may contribute to academic difficulties some children face.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
94
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(106 citation statements)
references
References 77 publications
3
94
1
8
Order By: Relevance
“…4 Some studies have shown a higher SRBD p r e v a l e n c e i n s c h o o l s l o c a t e d i n l o w e r socioeconomic settings. 6,[12][13][14] Notwithstanding this, our findings did not show significant differences in SRBD prevalence or in the association between SRBD and academic performance between public and private schools.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…4 Some studies have shown a higher SRBD p r e v a l e n c e i n s c h o o l s l o c a t e d i n l o w e r socioeconomic settings. 6,[12][13][14] Notwithstanding this, our findings did not show significant differences in SRBD prevalence or in the association between SRBD and academic performance between public and private schools.…”
Section: Discussioncontrasting
confidence: 56%
“…In this context, Galland et al have recently demonstrated, using a meta-analysis approach, that SRBD was associated with poor academic performance in Language Arts, Math, and Science and learning difficulties. 13 In addition, in Chile, Brockmann et al observed a strong association between SRBD and a low academic performance in Language Arts and Physical Education; however, it was not possible to determine such association with Math and Science. 4 In the study sample, SRBD prevalence was 24.6%, which was higher than what had been observed in previous studies conducted in other Chilean cities (18%).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several, but not all, studies have suggested that treatment of SDB leads to significant improvements in, or even to normalization of, cognitive performance if timely intervention is implemented (20)(21)(22)(23). Across these studies, it has been implied that, for children with SDB, disruption in attention and executive function skills, as well as challenges with aspects of behavioral regulation, are associated with explicit challenges with consolidating learning, both in the classroom and at home (24). As such, cognitive dysfunction situates as a particular neurodevelopmental concern, given its impact on successful achievement of learning goals, as well as the development of adaptive skills that support independence over time.…”
mentioning
confidence: 99%
“…En este contexto, Galland y cols., recientemente demostraron, mediante un abordaje metaanalítico, que los TRS se asociaban con un pobre rendimiento académico en áreas de Lenguaje, Matemática y Ciencias, así como también con dificultad para el progreso del aprendizaje. 13 Adicionalmente, en Chile, Brockmann y cols., observaron una fuerte asociación entre TRS y un bajo rendimiento académico en las áreas de Lenguaje y Educación Física; sin embargo, no fue posible establecer esta asociación con las áreas de Matemática y Ciencias. 4 En la muestra de estudio, la prevalencia de TRS fue de 24,6%, lo cual es superior a lo observado en investigaciones previas realizadas en otras ciudades de Chile (18%).…”
Section: Discussionunclassified
“…4 A l g u n o s e s t u d i o s h a n m o s t r a d o u n a mayor prevalencia de TRS en establecimientos educacionales de niveles socioeconómicos más bajos. 6,[12][13][14] Sin embargo, nuestros resultados no arrojaron diferencias significativas ni en la prevalencia de TRS ni en la asociación entre TRS y rendimiento académico entre establecimientos públicos y privados.…”
Section: Discussionunclassified